Effects of Agaricus blazei polypeptide on cell senescence by regulation of Keap1/Nrf2/ARE and TLR4/NF-κBp65 signaling pathways and its mechanism in D-gal-induced NIH/3T3 cells. (September 2020) - Feng, Qingxia; Lu, Xuechun; Yuan, Guangxin; Zhang, Qian; An, Liping
Graphical abstract: Highlights: Three active components ABp-RRQ, ABp-RQR and ABp-TRAR were obtained. ABp-RQR was the main active component to alleviate the oxidative inflammatory reactions. ABp-RQR play an anti-aging role by regulating Nrf2/ARE and TLR4/NF-κBp65 pathways. Abstract: Agaricus blazei is a kind of fungus plant with an edible as well as a medicinal use. Previous experiments have shown its crude peptide to possess an obvious anti-aging effect. In the present study three active components viz . ABp-RRQ, ABp-RQR and ABp-TRAR were obtained from the Agaricus blazei polypeptide. ABp-RQR was the main active component with a molecular weight of 458 Dalton, and HPLC confirmed it's a purity > 98%. When the D-galactose(D-gal)-induced NIH/3T3 cells were treated with ABp-RQR, changes were observed in the oxidative stress activities and the contents of inflammatory factors. Cell morphology and the percentage of positive cells were observed using the β-galactosidase staining. Western blot was used to detect the expression levels of the proteins modulated in the inflammatory and antioxidant signaling pathways. Our study suggests that ABp-RQR may play an anti-aging role by alleviating the oxidative inflammatory reactions in D-gal-induced NIH/3T3 cells.